An economic evaluation of operational decisions – an application in scheduling evaluation in fertilizer plants. Issue 9 (4th July 2021) - Bara, Najat; Gautier, Frédéric; Giard, Vincent
Abstract: Operational management is based on decisions that are related to the way resources are used in the short run. Reviewing the choice between several alternative operational decisions requires proper economic evaluation. The information provided by traditional cost accounting is not suitable for direct use at the operational decision-making process. We present an approach that requires identifying the physical consequences of the decisions being assessed, identifying relevant activity driver measures, establishing the material balance and estimating the differential cost by using relevant cost information. We illustrate our proposed approach with a real-life example of fertilizer production order scheduling on parallel and heterogeneous production lines in OCP's integrated supply chain. The results show that the use of management accounting outputs leads to a biased evaluation of the financial consequences of the decisions. Finally, we point out the relevance of the use of our economic evaluation approach in a decision support system context.